Application of the communication skills program for the peaceful resolution of conflicts in the classroom of the fifth grade of I.E. María Ugarteche de Mac Lean de Tacna of the year 2011. - Mayta Mamani, Yeni Gladys (2013)
Objetive: Determine whether the application of  "Communication Skills Program" improves the peaceful  resolution of conflicts in the classroom of girls in the fifth  grade of the I.E. "Maria Ugarteche de Mac Lean" school of  Tacna. Method: Using quasi-experimental design,  "Communication Skills Program" was applied to the  experimental group and a program evaluation  questionnaire as well; and pre-test questionnaires and  post-test to the experimental and control groups; 60 girls  in the fifth grade of primary education were part of the  research.  Result: Considerable improvement as to the “Active  Listening”, significantly improves of “assertiveness”. The  “Techniques for confront conflicts” have high increment,  resolving the conflict through a collaborative approach.  Conclusion: The development of communication skills  for the peaceful resolution of conflicts in the classroom,  improvement in the experimental group of girls in the fifth  grade of primary of I.E. "Mary Mac Lean Ugarteche" and  is superior to the control group, after applying the  program. It is effective and statistically significant